Left atrium assessment. Issue 10 (October 2015) - Panovsky, Roman; Pleva, Martin; Feitova, Vera; Kruzliak, Peter; Meluzin, Jaroslav; Kincl, Vladimir; Novotny, Petr; Vanicek, Jiri
<x xml:space="preserve">Abstract</x> The left atrium plays an integral role in cardiac performance. Data regarding the left atrial size, volume, function, and structure are clinically important in the management of patients with different diagnoses. Moreover, left atrial size and function were recognized as robust predictors of poor outcome across a broad range of cardiac diseases. These data are usually obtained using echocardiography. MRI can be used as an alternative tool or in clinical or experimental situations when more exact and detailed assessment is required. In the left atrial functional analysis, MRI is considered to be a gold standard technique that overcomes many of the limitations associated with echocardiographic assessment. In comparison with the other techniques, late gadolinium enhancement provides a unique opportunity to assess left atrial myocardial tissue in vivo. Complex cardiac magnetic resonance data may help to make a diagnosis, determine a prognosis and provide an impact on therapeutic actions. This review summarizes the potential role of cardiac magnetic resonance in left atrium assessment, with special emphasis on recent data and the potential future research directions.